Pengaruh Modifikasi Alat Latihan Terhadap Reaksi Penjaga Gawang Futsal Universitas Muhammadiyah Palopo - Pangestu, Galeh; Riswanto, A. Heri; Galugu, Nur Saqinah (Jurnal Porkes, 2025)
This study aims to determine the effect of modification of training tools on goalkeeper reactions. The population in the study were all UMP Palopo goalkeepers totaling 10 goalkeepers. The sample in this research was taken with total sampling technique. Based on the results of descriptive statistical tests, it shows that the pretest value gets a minimum average value of 2.264 and a maximum average value of 4.490 with a mean value of 3.18680, with a standard deviation of .845943, while that the posttest value gets a minimum average value of 6.341 and a maximum average value of 11.195 with a mean value of .8.31150 with a standard deviation of 1.421937. The average value of the posttest is higher than the pretest average value, meaning that there is a contribution to the effect of training tool modifications on the reaction of futsal goalkeepers. It can be concluded that the modification of training tools on goalkeepers can improve the reaction of futsal goalkeepers on the campus of Muhammadiyah University of Palopo there is an effect of modifying training tools on goalkeepers in improving goalkeeper reactions.